Pharmacological screening and isolation of bioactive compounds from plants used against elephantiasis in the Eastern Cape, South Africa - Adams, Zanele (University of the Free State, 2023)
Elephantiasis, also known as lymphatic filariasis, is a medical condition brought on by parasitic worms that invade the lymphatic system causing obstructions of lymph fluid in the passaged that is associated with excessive swelling of the lower and upper limbs resulting in disability, swelling of genitalia and breasts. The condition is also associated with non-filarial causes including certain sexually transmitted diseases, tuberculosis, leishmaniasis, leprosy and podoconsiasis. The World Health Organization lists the illness as one of the neglected tropical diseases that primarily affects developing nations. Although no precise figures have been provided, South Africa is one of the African nations where incidences of the illness have been reported. Plants are reported in treating several medical conditions that affect human kind. Traditional medicine has been considered as an alternative to Western medicine as it is easily accessible and the latter being more expansive. The continued use of plant medicine creates the need to identify those substances that are responsible for the biological activity or the healing properties found in plant extracts through scientific validation. Plants are used by indigenous people and traditional healers in different areas to treat the similar or different conditions. South Africa has a wide variety of plants, and traditional plant studies is reported in literature. In three municipalities of the OR Tambo District Municipality in the Eastern Cape of South Africa, an ethnobotanical survey on medicinal plants used in the management and treatment of lymphatic filariasis was carried out. A total of 29 therapeutic plants from 25 different Angiosperm families were recorded. Acokanthera oblongifolia Curtisia dentata, Dioscorea sylvatica, Elephantorrhiza elephantina, Gunnera perpensa, Hypoxis hemerocallidea, Pentanisia prunellloides and R. melanophloeos were reported as the most used plants in the study to treat elephantiasis and various ailments. The roots followed by the leaves and stem bark were the most used plant parts with infusions and decoctions being reported as the most frequently methods of administration. In vitro studies such as antimicrobial activity, antioxidant activity, phytochemical analysis, anti-inflammatory activity and cytotoxicity activity on mammalian cells were investigated. Bioactive compounds were also isolated and identified from K. drepanophylla.
Thesis (Ph.D.(Botany))--University of the Free State, 2023
Keywords: Elephantiasis; Lymphatic filariasis; Medicinal plant extracts; Antimicrobial screening; Phytochemical substances; Antioxidant activity; Anti-inflammatory activity; Cytotoxicity; O. R. Tambo District Municipality, South Africa; Ethnobotanical surveys; Angiosperm plant families